PRODUCTION OF ELECTRICITY BY SOLAR STIRLING ENGINE - PROF.GOPAL REDDY K; PRAJWAL.C; MANOJ RAMADHYANI; NIMISHAMBHA (International Journal of Innovations in Engineering Research and Technology, 2021)
The Stirling engine is both practically and theoretically a significant device, its practical virtue is simple, reliable and safe. The engine operates on a closed thermodynamic cycle, which is reversible. Today Stirling cycle-based systems are in commercial use as a heat pump, cryogenic refrigeration and air liquefaction. As a prime mover, Stirling cycles remain the subject of research and development efforts. A number of attempts have been made to build and improve the performance of Stirling engines. For successful operation of engine system with good efficiency, a careful design of heat exchangers, proper selection of drive mechanism and engine configuration is essential. Our Discussion indicates that a Stirling cycle engine working with relatively low temperature with air of helium as working fluid is potentially attractive engines of the future, especially solar-powered low-temperature differential Stirling engines with vertical, double acting, and gamma configuration. It is pollution free engine and use of any type of fuel characteristics and it shows a greater potential over any other type of engine existing today. This paper represents adetailed review of the past efforts taken for the development of the Stirling cycle engine and techniquesused for engine analysis.